2009
DOI: 10.1002/mc.20515
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of anandamide by COX‐2 is necessary for endocannabinoid‐induced cell death in tumorigenic keratinocytes

Abstract: Nonmelanoma skin cancer is the most prevalent cancer in the United States with approximately 1.25 million new cases diagnosed each year. Cyclooxygenase-2 (COX-2) expression is commonly elevated in these and other epithelial tumors. Cyclooxygenases metabolize arachidonic acid to prostaglandins, which promote growth and survival of tumor cells. COX-2 also metabolizes endocannabinoids forming prostaglandin-ethanolamides (PG-EA); however, the role of these lipid molecules in tumor cell survival is unclear. The goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…In the current study we have provided direct genetic evidence that establishes sensitivity to anandamide-induced cell death is dependent on COX-2 expression, a finding recently supported by a study in murine squamous carcinoma cells (44). The importance of COX-2 in the response to anandamide is emphasised by the fact that COX-2 is over-expressed in the majority of colorectal carcinomas (85%), and in a large population of colorectal adenomas (40-50%) (29), suggesting that anandamide treatment may be of benefit both in chemoprevention as well as treatment of advanced disease.…”
Section: Discussionsupporting
confidence: 71%
“…In the current study we have provided direct genetic evidence that establishes sensitivity to anandamide-induced cell death is dependent on COX-2 expression, a finding recently supported by a study in murine squamous carcinoma cells (44). The importance of COX-2 in the response to anandamide is emphasised by the fact that COX-2 is over-expressed in the majority of colorectal carcinomas (85%), and in a large population of colorectal adenomas (40-50%) (29), suggesting that anandamide treatment may be of benefit both in chemoprevention as well as treatment of advanced disease.…”
Section: Discussionsupporting
confidence: 71%
“…82,88 As noted above, PG-EAs and PG-Gs are resistant to degradation by 15-hydroxyprostaglandin dehydrogenase when compared to their free acid counterparts. Thus, it is conceivable that these compounds could serve as a more metabolically stable pool of PGs that is transported to distant sites prior to hydrolysis and receptor binding.…”
Section: Cross-talk Between the Endocannabinoid And Eicosanoid Signalmentioning
confidence: 89%
“…Recently we showed that AEA-induced cytotoxicity was mediated by the production of proapoptotic, J-series prostaglandins in tumorigenic keratinocytes that overexpress COX-2 (Van Dross, 2009;Kuc et al, 2012). In addition, resistance to AEA-induced cytotoxicity was observed in non-tumorigenic keratinocytes with low basal COX-2 expression however, these cells underwent cell death when transfected with an expression plasmid containing COX-2.…”
Section: Endocannbinoids and Cycloxygenase-2 (Cox-2) In Cancermentioning
confidence: 99%
“…Blockade of AEA degradation by inhibiting FAAH increased J-series prostaglandin synthesis and apoptosis. Also, the cytotoxic effect of AEA was not blocked by CB1R, CB2R or TRPV1 antagonists (Van Dross, 2009). Thus, AEA-induced cell death in tumor cells which overexpress COX-2 appears to be caused by the conversion of AEA to cytotoxic prostaglandins (Van Dross, 2009;Kuc, Jenkins, and Van Dross, 2012;Patsos et al, 2010; Pastos et al, 2005).…”
Section: Endocannbinoids and Cycloxygenase-2 (Cox-2) In Cancermentioning
confidence: 99%